Barriers and characteristics for successful transition to adult healthcare for individuals with cerebral palsy: a systematic review. (3rd September 2019) - Lilly, Hannah; Bitzel, Mackenzie; Pejnovic, Tatiana; Schnell, Joanna; Doty, Antonette
Abstract: Background: Cerebral palsy (CP) is a common childhood disability. However, these individuals are now living longer lives, participating in adult roles, and seeking healthcare services. The transition from pediatric to adult healthcare for adolescents with CP is a challenging yet significant time. Adolescents experience several barriers during transition. Objectives: To utilize the environmental and personal dimensions of the ICF model in order to explore barriers when transitioning to adulthood as well as discuss characteristics and physical therapy implications needed to succeed within transition. Methods: Electronic searching of PubMed, CINAHL, ERIC, Scopus, ProQuest, and the Cochrane Library databases was concluded on January 9, 2019 for studies including transition between pediatric and adult healthcare in individuals diagnosed with CP. Two independent reviewers agreed upon inclusion, eligibility, and quality assessment of each study using the Mixed-Methods Appraisal Tool (MMAT). Results: Seven studies were included in the systematic review. Results for each study were separated based on the personal and environmental contextual factors of the ICF model and solutions to the barriers were then discussed. Conclusions: Research has provided proposed solutions to select barriers, however, other barriers have yet to be addressed. More research is needed to address these barriers and provide a model program that can be implemented within the healthcare systems to promote a successful transition for adolescents with CP from pediatric to adult services.